1990
DOI: 10.1107/s0108270190001615
|View full text |Cite
|
Sign up to set email alerts
|

Structure of putrescinium dihydrogendiphosphate

Abstract: 2+ 2-C4HI4N2 . H2P207, Mr = 266"1, monoclinic, C2/c, a = 16-569 (2), b --8.4497 (6), c = 7.998 (1)A, # =96"282 (9) °, V= 1113.0 (2)A), Z= 4, Dm= 1.570, Dx = 1.587 g cm -3, A(Mo Ka) = 0.71069/~, /z --3.49 cm-1, F(000) = 560, T = 290 K, R = 0.030 for 862 observed reflections. The putrescinium dication is located on a center of symmetry and has the extended all-trans conformation. The dihydrogendiphosphate anion is located on a twofold axis with the bridge P--O---P angle 134.26 (7) ° and the two PO3 groups stagge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Distances (C--C, N--C) and angles (N--C--C, C--C--C) relating to the conformation of the organic dication are reported in Table 2. They are similar to the main geometric features of this organic group observed in other phosphoric anions [HPO42- (Kamoun & Jouini, 1990), H2P2072- (Bartoszak & Jaskolski, 1990), P4042 - (Thabet, Bdiri, Jouini & Durif, 1995)] 0 in that they lie within the ranges 1.481 (2)…”
Section: Commentsupporting
confidence: 77%
“…Distances (C--C, N--C) and angles (N--C--C, C--C--C) relating to the conformation of the organic dication are reported in Table 2. They are similar to the main geometric features of this organic group observed in other phosphoric anions [HPO42- (Kamoun & Jouini, 1990), H2P2072- (Bartoszak & Jaskolski, 1990), P4042 - (Thabet, Bdiri, Jouini & Durif, 1995)] 0 in that they lie within the ranges 1.481 (2)…”
Section: Commentsupporting
confidence: 77%
“…Each end of the pyrophosphate anion is hydrogen bonded to the nitrogen atoms of a m -xylyldiamine moiety through two of its oxygen atoms while the third oxygen atom, bearing a proton, points away from the cavity and is hydrogen bonded to a nitrogen atom of an adjacent molecule. The pyrophosphate oxygen−nitrogen bond distances range from 2.60 to 2.75 Å with an average of 2.67 Å and are comparable to similar pyrophosphate O···N distances. , The non-protonated secondary amines of the diethylenetriamine bridge also make close contacts with an oxygen atom of the pyrophosphate anion, N(2)−O(6) and N(5)−O(3), 2.68 and 2.72 Å respectively. Their proximity to the anion is noteworthy as it is these central amino nitrogen atoms of O-BISDIEN that are responsible for the nucleophilic attack on the bound polyphosphate substrate that leads to the catalytic hydrolysis of ATP in model systems …”
Section: Resultsmentioning
confidence: 68%
“…Further investigation indicated that this was a unique complex, containing both phosphoric acid and dihydrogen phosphate species, in addition to the macrocycle in the crystal structure. The crystal structures of dihydrogen phosphate and dihydrogen phosphate salts of acyclic polyamines have been published, , as well as two crystal structures of polyammonium macrocycles with pyrophosphate counterions. , To our knowledge, however, this is the first example of a crystal structure of a polyammonium macrocycle combined with either phosphoric acid or dihydrogen phosphate, not to mention both, in the same structure. Additionally, potentiometric studies indicate ditopic behavior for the macrocycle at low pHs, that is, the binding of two monohydrogen phosphates with one macrocycle.…”
Section: Introductionmentioning
confidence: 97%